Edukasi Perilaku “Cerdik” sebagai Upaya Pencegahan Penyakit Tidak Menular pada Lansia - Islamudin, Syarif Febrian; Maryoto, Madyo; Sumarni, Tri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Older adults are vulnerable to noncommunicable diseases (NCDs) due to the aging process, lifestyle changes, and lack of health knowledge. The high incidence of NCDs among older adults in Karangsembung Village has not been matched by adequate health education. The implementation of CERDIK behavior is seen as an effective strategy to raise awareness and prevent NCDs. Objective: This activity aims to increase the knowledge of the elderly regarding CERDIK behavior as an effort to prevent NCDs. Method: The activity methods included a pre-test, interactive education on CERDIK behavior, a post-test, and observation of the application of behavior in the elderly at the Manggis Health Center in Karangsembung Village. Result: The pre-test results showed that most participants’ knowledge was in the adequate category (47.4%), which increased to the good category (89.5%) after education. Implementation of CERDIK behavior was largely achieved, with 100% compliance in routine health checks, smoking cessation, light physical activity, healthy eating, healthy sleep, and stress management. However, knowledge regarding the dangers of smoking (52.6%) and adequate sleep (89.5%) remained suboptimal. Conclusion: These findings indicate that health education effectively improves knowledge and promotes positive preventive behaviors, though certain areas still require reinforcement.